Integral representation of even positive-definite functions of two variables - Lopotko, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We obtain integral representation of even functions of two variables, for which the kernel $[k_1( x + y) + k_2( x - y)],\quad x, y \in R^2$, is positive definite.